2020
DOI: 10.3390/polym12010159
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Bilayer PLA/Chitosan Nanofibrous Scaffolds Doped with ZnO, Fe3O4, and Au Nanoparticles with Bioactive Properties for Skin Tissue Engineering

Abstract: Burns affect almost half a million of Americans annually. In the case of full-thickness skin injuries, treatment requires a transplant. The development of bioactive materials that promote damaged tissue regeneration constitutes a great alternative to autografts. For this reason, special attention is focused on three-dimensional scaffolds that are non-toxic to skin cells and can mimic the extracellular matrix, which is mainly composed of nanofibrous proteins. Electrospinning, which enables the preparation of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…In recent years, hybrid nanomaterials composed by biopolymers and inorganic nanoparticles have attracted growing interest within several fields, including biomedicine [ 1 , 2 , 3 , 4 , 5 ], pharmaceutics [ 6 , 7 , 8 , 9 , 10 ], food packaging [ 11 , 12 , 13 , 14 , 15 ], remediation [ 16 , 17 ] and cultural heritage [ 18 , 19 , 20 ]. As evidenced in a recent review [ 21 ], both ionic and non-ionic polysaccharides can be suitable polymers for the development of functional nanocomposites, with excellent performances in terms of thermal stability, barrier properties and mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hybrid nanomaterials composed by biopolymers and inorganic nanoparticles have attracted growing interest within several fields, including biomedicine [ 1 , 2 , 3 , 4 , 5 ], pharmaceutics [ 6 , 7 , 8 , 9 , 10 ], food packaging [ 11 , 12 , 13 , 14 , 15 ], remediation [ 16 , 17 ] and cultural heritage [ 18 , 19 , 20 ]. As evidenced in a recent review [ 21 ], both ionic and non-ionic polysaccharides can be suitable polymers for the development of functional nanocomposites, with excellent performances in terms of thermal stability, barrier properties and mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation rate of polymeric scaffolds strongly correlates with the material composition, the polymer molecular architecture (e.g., side groups, aromatic groups, double or triple bonds, and crosslinking), and the fabrication method (e.g., blending and copolymerization), which controls the degree of chain scission (Liu et al, 2012 ; Ferrari et al, 2017 ; Ferreira et al, 2019 ; Keirouz et al, 2020 ; Sadeghi-avalshahr et al, 2020 ) and modulates the biodegradability, hydrophilicity, and biocompatibility as well as cell adhesion, proliferation, growth, and antibacterial activity in TE applications (Gao et al, 2019 ). Polymer crosslinking reduces the degradation rate (Bi et al, 2011 ; Kishan et al, 2015 ; Chen et al, 2020 ), whereas the incorporation of a high fraction of nanoparticles (NPs) to play the role of bioactive sites in the scaffold may increase the degradation rate (Mehrasa et al, 2016 ; Radwan-Pragłowska et al, 2020 ), although some studies have shown an opposite effect (Mehrasa et al, 2016 ; Park et al, 2018 ). The degradation rate can also be tuned by chemical modification methods or by adding NPs that can neutralize acidic products (Zhang H. et al, 2014 ; Shuai et al, 2019 ).…”
Section: Scaffold Main Characteristicsmentioning
confidence: 99%
“…Importantly, the size of NPs is critical because extremely small particles can penetrate the cell membrane, leading to the formation of vacuoles and, ultimately, premature apoptosis, or aggravate a chronic inflammatory response. Examples of the promising usage of particles in scaffold engineering include fibrous electrospun constructs synthesized from PCL and gelatin blends doped with MgO particles that resulted in 79% wound size reduction when seeded with human endometrial stem cells in vitro compared to 11% size reduction accomplished with sterile gauze control ( Figure 7D ) in addition to improved mechanical properties (Ababzadeh et al, 2020 ); 3D printed structures of PCL/poly(propylene succinate) copolymer doped with AgNO 3 demonstrating improved degradation behavior, cell viability, and antimicrobial properties compared to PCL scaffolds (Afghah et al, 2020 ); electrospun scaffolds of chitosan/gelatin with Fe 3 O 4 NPs demonstrating enhanced mechanical properties and antibacterial activity (Cai et al, 2016 ); and scaffolds functionalized with conductive NPs, such as ZnO, Fe 3 O 4 , Au, Ag, and TiO 2 , which enhanced cell proliferation, adhesion, and migration by means of electrical stimulation, or surface roughening by the particles at the scaffold surface (Babitha and Korrapati, 2017 ; Zulkifli et al, 2017 ; Kianpour et al, 2020 ; Radwan-Pragłowska et al, 2020 ).…”
Section: Recent Progress In Scaffolds For Skin and Brain Tissue Engineeringmentioning
confidence: 99%
“…Hybrid bilayer PLA/ nanofibrous chitosan scaffolds containing ZnO, Fe 3 O 4 , and Au nanoparticles have bioactive properties in skin tissue engineering applications for the treatment of full‐thickness skin injuries. [ 112 ] This polymer displayed electroconductive properties and minimal cytotoxity and was suitable for the treatment of severe burn patients. Black TiO 2 nanotubes have been investigated as electrodes in electric field‐induced stimulation of stem cell growth in osteogenic applications.…”
Section: Electro‐stimulation and The Development Of Conductive Bioscamentioning
confidence: 99%